Terracotta Figures, Figurines, and Plaques from the Anavlochos, Crete. - Florence Gaignerot-Driessen (Les Carnets de l’ACoSt)
In the summer of 2017 two votive deposits were excavated on the summit of the Anavlochos, Crete. The first one yielded protogeometric to classical figures, figurines, and plaques representing female figures. The second one included zoomorphic figures and figurines associated with Late Minoan IIIC pottery. In addition, the head of a female figure was recovered from a shrine that was brought to light on the slope of Kako Plaï, just above a third votive deposit, that already had been excavated by Pierre Demargne in 1929.